Atezolizumab and Bevacizumab Attenuate Cisplatin Resistant Ovarian Cancer Cells Progression Synergistically via Suppressing Epithelial-Mesenchymal Transition - Zhang, Lei; Chen, Ying; Li, Fangxuan; Bao, Lewen; Liu, Wenxin (Frontiers in Immunology, 2019)
The AURELIA trial demonstrated that adding Bevacizumab to chemotherapy significantly improved progression-free survival (PFS) for platinum resistant recurrent ovarian cancer. Recently, immunotherapy also presented potential anti-tumor effects in several malignant solid tumors. This study aimed to investigate whether combining anti-PD-L1 Atezolizumab with BEV may have a synergistic effect and enhance the efficacy of both treatments in cisplatin resistant epithelial ovarian cancer (CREOC). We retrospectively analyzed 124 epithelial ovarian cancer (EOC) patients from Gynecologic Oncology Department of Tianjin Cancer Hospital between January 2013 and June 2018, who all were diagnosed with cisplatin resistance due to progressing < 6 months after completing platinum-based therapy. Based on responding to at least 2 cycles of Bevacizumab-containing chemotherapy (BC), these Patients were divided into BC response group and BC non-response group. Immunohistochemistry was used to detect that PD-L1 expression and tumor angiogenesis-related proteins (VEGF and Semaphorin4D) in tissues from 124 patients with CREOC. The positive expressions of PD-L1, VEGF, and Semaphorin4D (SEMA4D) were found in 58.73%, 50.79%, and 71.43% of the 63 cases CREOC tissues with BC response, respectively, which were significantly higher than that in the 61 cases BC non-response group (P<0.05). PD-L1 expression correlated with SEMA4D and VEGF positively (r=0.344 and 0.363, P<0.001). Over-expressions of PD-L1, VEGF and SEMA4D are associated with more malignant clinicopathologic characteristics of CREOC Patients. In survival analysis, patients’ response to BC was the independent factor for evaluation of PFS and overall survival (OS). Cell functional assays showed that Atezolizumab in combination with Bevacizumab inhibited the proliferation, migration, and invasion of cisplatin resistant ovarian cancer cell line A2780cis in vitro synergistically, which maybe associate with Bevacizumab suppressing the epithelial-mesenchymal transition (EMT) and PD-L1 expression by targeting STAT3. Furthermore, Bevacizumab and Atezolizumab induced synergistic anti-tumor effect in vivo. These findings suggest a novel therapeutic strategy for cisplatin resistant recurrent EOC and its mechanism warrants further study.